Is There a Role for Laparoscopic Adrenalectomy in Patients with Suspected Adrenocortical Carcinoma? A Critical Appraisal of the Literature - Jurowich, C.; Fassnacht, M.; Kroiss, M.; Deutschbein, T.; Germer, C.-T.; Reibetanz, J. (Hormone and Metabolic Research, 2013)
Adrenocortical carcinoma (ACC) is a rare endocrine neoplasm and complete resection is the only treatment with curative intent for patients with nonmetastatic disease. It is highly debatable whether minimally invasive surgery is oncologically equal to open procedures in these patients. This review summarizes the current knowledge on the feasibility and oncological effectiveness of laparoscopic surgery for ACC. Using a Pubmed search strategy covering the time period up until July 2012, we identified 568 original articles and reviews with the following search terms: “adrenal gland neoplasms” and “laparoscopy“, with restriction to patients over 18 years of age. Finally, 23 publications, including 6 “key studies”, became the basis of this review. The key papers described 673 patients with localized ACC, of whom 112 had laparoscopic surgery. Acknowledging the subjectivity of our personal view, we draw the following conclusions: 1) since all available studies are retrospective, a final judgment of laparoscopic surgery in ACC cannot be provided; 2) the surgical treatment of patients with (suspected) ACC should be limited to specialized centers; and 3) For tumors of limited size (<10 cm) without evidence of invasiveness, laparoscopic adrenalectomy does not seem to be oncologically inferior to open surgery when performed in a state of the art manner and when oncological standards (margin-free resection, avoidance of tumor spillage) are respected. However, open adrenalectomy should still be regarded as standard treatment for ACC and laparoscopic surgery should be performed within a clinical trial or at least as an observational study.
Keywords: adrenocortical carcinoma; laparoscopic surgery; oncology